The mycobacterial ABC transporter IrtAB employs a membrane-facing crevice for siderophore-mediated iron uptake - Imre Gonda; Simona Sorrentino; Laura Galazzo; Nicolas P. Lichti; Fabian M. Arnold; Ahmad R. Mehdipour; Enrica Bordignon; Markus A. Seeger (Nature Communications)
Abstract The mycobacterial ABC transporter IrtAB features an ABC exporter fold, yet it imports iron-charged siderophores called mycobactins. Here, we present extensive cryo-EM analyses and DEER measurements, revealing that IrtAB alternates between an inward-facing and an outward-occluded conformation, but does not sample an outward-facing conformation. When IrtAB is locked in its outward-occluded conformation in nanodiscs, mycobactin is bound in the middle of the lipid bilayer at a membrane-facing crevice opening at the heterodimeric interface. Mutations introduced at the crevice abrogate mycobactin import and in corresponding structures, the crevice is collapsed. A conserved triple histidine motif coordinating a zinc ion is present below the mycobactin binding site. Substitution of these histidine residues with alanine results in a decoupled transporter, which hydrolyzes ATP, but lost its capacity to import mycobactins. Our data suggest that IrtAB imports mycobactin via a credit-card mechanism in a transport cycle that is coupled to the presence of zinc.